Elaine Stritch at liberty / [videorecording (DVD)] - Stritch, Elaine (Kultur : Digital Classics (Firm), 2013)
Elaine Stritch at Liberty, the Broadway legend's one-woman show, triumphed in New York and won a 2002 Tony Award. This double-Emmy-winning recording was made when she later took London by storm. Stritch's comic timing is impeccable and her anecdotes priceless as she talks and sings her way through fifty years in American theatre. From a disastrous date with Marlon Brando to blowing her chance of starring in The Golden Girls, she is uncompromisingly honest in telling her own story.